Avaliação de propriedades mecânicas e características metalúrgicas da liga multicomponente Cr₄₀Co₃₀Ni₃₀ processada em escala semi-industrial - Pereira, Vitor Deghaid (2021)
Differently from the classic concept of alloy design, which is based on selecting a main element and adding others to guarantee specific properties, a new strategy has been used in recent years for the so-called multicomponent alloys or high entropy alloys, which do not have a single main element. The most famous and commonly studied was the Brian Cantor’s alloy Fe20Cr20Mn20Ni20Co20, which shows a face centered cubic structure and excellent properties at room and cryogenic temperatures. Further studies showed that the ternary equiatomic alloy Cr33Co33Ni33 had a strength and ductility combination superior to that of the quinary alloy, indicating that the mechanical strength is not only a function of the number of elements, but also of the type of element used, with Cr being the most promising in increasing the alloy strength. Based on previous research, the Cr40Co30Ni30 (% atomic) alloy was chosen to be studied in this work. The composition was produced on a semi-industrial scale, in ingots weighing approximately 50 kg. The material was homogenized, hot worked by forging and rolling, heat treated and mechanically tested. The mechanical properties were evaluated by tensile, hardness and Charpy-V impact tests at ambient and cryogenic temperatures, on the hot formed and heat treated conditions. It was verified that the melting method and raw material purity used in the melting operation have a direct effect on the type and quantity of inclusions formed. Moreover, despite the material showing good mechanical properties, its production by hot forming is challenging, once it has a strong tendency to surface defects below 900oC.